2011
DOI: 10.1088/0004-637x/728/2/131
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Absorption Spectra of Protonated Anthracenes and Phenanthrenes, and Their Neutrals in Neon Matrices

Abstract: Electronic spectra of three isomers of protonated anthracene and five isomers of protonated phenanthrene have been detected in 6 K neon matrices following deposition of mass-selected m/z = 179 cations produced from dihydro-anthracene or-phenanthrene. The cations exhibit moderately intense band systems in the 400-550 nm range. Corresponding neutrals have been observed in the UV. The absorptions are assigned to specific isomers of the protonated species on the basis of time-dependent density functional theory ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 29 publications
4
33
2
Order By: Relevance
“…The hydrogenated protonated quinolines have been formed by the soft method of electrospray ionization where the molecules are very unlikely to break apart. Protonation of PAHs by electrospray ionization have previously been reported (Knorke et al 2009;Vala et al 2009;Garkusha et al 2011;Szczepanski et al 2011;Vala et al 2011), but here we show that up to full hydrogenation of the edge sites occur. Cationic states of highly hydrogenated pentacene are generated in the harsh environment of the Nielsen plasma ion source, thus demonstrating very high stability.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The hydrogenated protonated quinolines have been formed by the soft method of electrospray ionization where the molecules are very unlikely to break apart. Protonation of PAHs by electrospray ionization have previously been reported (Knorke et al 2009;Vala et al 2009;Garkusha et al 2011;Szczepanski et al 2011;Vala et al 2011), but here we show that up to full hydrogenation of the edge sites occur. Cationic states of highly hydrogenated pentacene are generated in the harsh environment of the Nielsen plasma ion source, thus demonstrating very high stability.…”
Section: Discussionsupporting
confidence: 57%
“…Both computational and experimental results show that protonation and hydrogen addition strongly influence the optical spectra (Pathak & Sarre 2008;Chakraborty et al 2009;Hammonds et al 2009;Ricks et al 2009;Knorke et al 2009;Garkusha et al 2011;Alata et al 2010;Bonaca & Bilalbegovic 2011). This indicates that, although bare and singly protonated PAHs can be ruled out as carriers of the DIBs (Steglich et al 2011), hydrogenated PAHs cannot.…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been shown that both N-substitution ) and protonation of PAHs (Alvaro Galué et al 2010) introduce blue shifts in the IR emission features, giving a better fit to the UIR features attributed to PAHs. A direct comparison of our H + PANH spectra with H + PAH spectra of anthracene-9H and phenanthene-9H (Garkusha et al 2011) reveals blueshifts of ∼11 and 133 nm, respectively, due to the presence of N in the ion. The destabilising effect of N on the ion in its excited state is particularly marked for phenanthridine.…”
Section: Astrophysical Implicationsmentioning
confidence: 79%
“…(1) Lambert et al (1984); (2) protonated naphthalene (Alata et al 2010a), anthracene (Alata et al 2010b;Garkusha et al 2011), phenanthrene (Alata 2012;Garkusha et al 2011), fluorine (Alata et al 2012), tetracene (Alata et al 2010b), pyrene (Alata 2012;Garkusha et al 2011;Hardy et al 2013) and coronene (Garkusha et al 2011;Rice et al 2014). Protonation of aromatic heterocycles shifts the absorption spectra to lower energy, but to a smaller extent than for the fully carbonated analogues: for example acridineH + is red shifted by 0.4 eV from acridine, while anthraceneH + is red shifted by 0.9 eV from neutral anthracene (see Table 1).…”
Section: Three-ringed Protonated Panhsmentioning
confidence: 99%
See 1 more Smart Citation